Thermal waters of 'tectonic origin': the alkaline, Na‐HCO3 waters of the Rio Valdez geothermal area (Isla Grande de Tierra del Fuego, Argentina). Issue 1 (30th November 2012) - CAPACCIONI, BRUNO; MENICHETTI, MARCO; RENZULLI, ALBERTO; TASSONE, ALEJANDRO; HUERTAS, ANTONIO D.
Abstract: The geothermal area of Rio Valdez is located in the central portion of the Isla Grande de Tierra del Fuego (South Argentina), ten kilometers south of the southeastern sector of the Fagnano Lake. It consists of a series of thermal springs with low discharge rates (≤1 L/s) and temperatures in the range of 20–33°C distributed in an area of <1 km 2 . The thermal springs are characterized by alkaline, Na‐HCO3 waters with low salinity (0.53÷0.58 g/L), but relatively high fluoride contents (up to 19.4 mg/L). Their composition is the result of a slow circulation at depth, possibly through deep tectonic discontinuities connected with the Magallanes‐Fagnano Fault (MFF) system. According to geothermometric calculations, thermal waters reach temperatures in the range of 100–150°C and an almost complete chemical equilibrium with the alkali‐feldspars in the metavolcanic country rocks. The relatively high fluorine contents can be explained by the slow ascent and cooling of deep groundwaters followed by a progressive re‐equilibration with F‐bearing, hydrated Mg‐silicates, such as chlorite, which has been recognized as an abundant mineral in the metavolcanics of the Lemaire Formation and metapelites and metagraywackes of the Yahgán Formation. Finally, the isotopic composition of the investigated samples is consistent with the infiltration from local snow melting at altitudes in the range of 610–770 m asl. The comparison of our data with those collected in 1991 seems to suggest a possible progressive decline of the bulk thermal output in the near future. This possibility should be seriously considered before planning a potentially onerous exploitation of the resource. Presently, the only ways to exploit this geothermal resource by the population scattered in the area are the direct use of thermal waters and/or spa structures.